Una nueva especie de rana de cristal del género Hyalinobatrachium (Anura: Centrolenidae) del Delta del Río Orinoco, Venezuela - Señaris, J Celsa; Ayarzagüena, José (Revista de Biología Tropical, 2001)
A new species of Hyalinobatrachium of the fleischmanni group, H. mondolfii, is described from the Orinoco delta floodplains in Venezuela. This new species can be distinguished from other congeners by the following combination of characters: parietal peritoneum clear, pericardium white, visceral and hepatic peritoneum white, color in life pale green with diminute yellow spots and, in preservative, cream with small dark melanophores (visible only under magnification), bones white in life, extense webbing, snout round in dorsal view and inclinate in lateral view, dorsal skin granulate and a advertisement call with a fundamental frequency greater than 5000 Hz.